2010
DOI: 10.1089/jpm.2009.0363
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acupressure in Symptom Management in Patients with End-Stage Renal Disease: A Systematic Review

Abstract: No definitive conclusion is available. Future trials should adhere to standards of trial methodology and explicitly report relevant information for evaluation of efficacy and safety of acupressure in patients with ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Dolayısıyla KBY hastaları geleneksel tedavilerle yönetilmesi zor olan, hastalığa bağlı kronik ağrı, kaşıntı, yorgunluk ve uyku bozukluğu gibi yaşam kalitesini azaltan birçok rahatsızlık ve komplikasyon deneyimlerler 3 . Bu durumla baş edebilmek için de % 25.2 ile % 57 arasında değişen oranlarda TAT yöntemlerine başvurmaktadırlar 2,11,12,13,14,15 .…”
Section: Introductionunclassified
“…Dolayısıyla KBY hastaları geleneksel tedavilerle yönetilmesi zor olan, hastalığa bağlı kronik ağrı, kaşıntı, yorgunluk ve uyku bozukluğu gibi yaşam kalitesini azaltan birçok rahatsızlık ve komplikasyon deneyimlerler 3 . Bu durumla baş edebilmek için de % 25.2 ile % 57 arasında değişen oranlarda TAT yöntemlerine başvurmaktadırlar 2,11,12,13,14,15 .…”
Section: Introductionunclassified
“…The third limitation was absence of an active control group. Moreover, the fourth limitation of this study was selection of the A c c e p t e d M a n u s c r i p t 14 patients from two local hospitals in one of the big cities of our country. Thus, the study results may not be generalizable to a typical community of ESRD patients with unidentified level of cardiovascular health, physical function, and different related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…12 Because of electrolyte imbalance and other factors, the patients on HD usually complain about pain, fatigue, muscle weakness 13 , and poor Quality Of Life (QOL). 14 In the recent years, it was reported that some ESRD patients used complementary and alternative therapies. 15 Relaxation therapy is known as a complementary therapy that relieves psychological distress in the patients with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Wristbands exhibited variable results in controlling the post-operative indications after urological endoscopic surgery 249 . In case of surgical interventions, acupressure is unable to provide complete relief to patients due to lack of total symptom management in end-stage renal disease (ESRD) 250 . In tonsillectomy, pre-operative acupressure and acupuncture fails to overcome emesis in children 251 .…”
Section: Limitationsmentioning
confidence: 99%